2012
DOI: 10.1007/s00404-012-2440-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sperm DNA fragmentation, apoptosis and dysfunction of mitochondrial membrane potential with semen parameters and ART outcome after intracytoplasmic sperm injection

Abstract: In the present study; DF, apoptosis and dysfunction of sperm MMP indicated negative relationship with sperm parameters. Although there was a negative correlation between early apoptosis and pregnancy rate, no significant correlation was observed between these parameters and ICSI outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 39 publications
0
27
0
4
Order By: Relevance
“…Several investigators observed lower sDNAfrag in men with higher sperm concentration, total motility, progressive motility and normal morphology (Belloc et al, 2014;Moskovtsev et al, 2009;Oosterhuis et al, 2000;Shen et al, 2002;Zhang et al, 2008), whereas others showed that these parameters are not correlated with sDNAfrag (Ricci et al, 2002). However, after use of sperm-preparation techniques, results appear more consistent, several reports finding that after swim-up the percentage of sDNAfrag was negatively correlated with motility and morphology (Lopes et al, 1998;Sharbatoghli et al, 2012), with the same results observed after the use of DGC (Sakkas et al, 1999). In relation to sperm pathologies, using DGC followed by wash and swim-up, a significant correlation between the degree of sDNAfrag and asthenozoospermia was not found, but a significantly higher percentage of sDNAfrag was reported in men with teratozoospermia (Mehdi et al, 2009).…”
Section: Tunel+ H-tunel+ Tunel+ H-tunel+ Concentrationmentioning
confidence: 76%
“…Several investigators observed lower sDNAfrag in men with higher sperm concentration, total motility, progressive motility and normal morphology (Belloc et al, 2014;Moskovtsev et al, 2009;Oosterhuis et al, 2000;Shen et al, 2002;Zhang et al, 2008), whereas others showed that these parameters are not correlated with sDNAfrag (Ricci et al, 2002). However, after use of sperm-preparation techniques, results appear more consistent, several reports finding that after swim-up the percentage of sDNAfrag was negatively correlated with motility and morphology (Lopes et al, 1998;Sharbatoghli et al, 2012), with the same results observed after the use of DGC (Sakkas et al, 1999). In relation to sperm pathologies, using DGC followed by wash and swim-up, a significant correlation between the degree of sDNAfrag and asthenozoospermia was not found, but a significantly higher percentage of sDNAfrag was reported in men with teratozoospermia (Mehdi et al, 2009).…”
Section: Tunel+ H-tunel+ Tunel+ H-tunel+ Concentrationmentioning
confidence: 76%
“…These studies were excluded from meta-analysis, because no cut-off values were used so a 2x2 table could not be constructed from the data. Some of these studies found an association between sperm DNA fragmentation and pregnancy [83,92,93,97,104,107], while others did not find an association between sperm DNA fragmentation and conception [47,116]. In conclusion, we think that the best way to judge the value of DNA fragmentation tests is by their predictive capacity for the outcome of interest, ongoing pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…We found 21 studies reported on the SCSA [103,110112,114,117,118,123136], 18 studies on the SCD test [97,98,101,102,106–109,113,115,116,120,122,137–141], 18 studies reported on the TUNEL assay [92–95,96,99,100,104,119,134,142149] and seven studies reported on the alkaline Comet assay [95,105,121,134,150152]. …”
Section: Resultsmentioning
confidence: 99%
“…Although Degheidy et al [41] reported that post-MACS samples showed no difference in sperm motility (80.6%±6.9%) compared with control samples (80.9%±7.7%), de Vantery Arrighi et al [42] reported that the progressive sperm motility of post-MACS semen samples (67.9%±3.8%, p <0.05) was significantly better than pre-MACS control samples (48.4%±2.4%). Additionally, other studies have reported a significant inverse correlation between apoptosis and progressive motility [434445]. Therefore, the positive effect of MACS on the isolation of sperm with high DNA integrity may result from the selection of non-apoptotic sperm with progressive motility.…”
Section: Discussionmentioning
confidence: 99%